IRF5 is a novel regulator of CXCL13 expression in breast cancer that regulates CXCR5+ B‐ and T‐cell trafficking to tumor‐conditioned media. Issue 5 (23rd December 2014) - Pimenta, Erica Maria; De, Saurav; Weiss, Ryan; Feng, Di; Hall, Kelly; Kilic, Sarah; Bhanot, Gyan; Ganesan, Shridar; Ran, Sophia; Barnes, Betsy J
Abstract : Clinical studies using prognostic and predictive signatures have shown that an immune signal emanating from whole tumors reflects the level of immune cell infiltration—a high immune signal linked to improved outcome. Factors regulating immune cell trafficking to the tumor, however, are not known. Previous work has shown that expression of interferon regulatory factor 5 (IRF5), a critical immune regulator, is lost in 80% of invasive ductal carcinomas examined. We postulated that IRF5‐positive and ‐negative breast tumors would differentially regulate immune cell trafficking to the tumor. Using a focused tumor inflammatory array, differences in cytokine and chemokine expression were examined between IRF5‐positive and ‐negative MDA‐MB‐231 cells grown in three‐dimensional culture. A number of cytokines/chemokines were found to be dysregulated between cultures. CXCL13 was identified as a direct target of IRF5 resulting in the enhanced recruitment of B and T cells to IRF5‐positive tumor‐conditioned media. The ability of IRF5 to regulate mediators of cell migration was confirmed by enzyme‐linked immunosorbent assay, chromatin immunoprecipitation assay, small interfering RNA knockdown and immunofluorescence staining of human breast tumor tissues. Analysis of primary immune cell subsets revealed that IRF5 specifically recruits CXCR5 + B and T cells to the tumor; CXCR5 is the receptor for CXCL13. Analysis of primary breast tumor tissues revealed a significant correlation between IRF5 and CXCL13 expression providing clinical relevance to the study. Together, these data support that IRF5 directly regulates a network of genes that shapes a tumor immune response and may, in combination with CXCL13, serve as a novel prognostic marker for antitumor immunity.